About Money and Other Important Things (Nominated play, excerpt) - Panayotova, Theodora (Sledva : NBU Journal of Humanities and Arts, 2020)
The characters of the play are students in 1st, 3rd and 5th grade who are friends from school and neighborhood. They are from different socio-economic backgrounds depending on their parents’ work and social status. They share their problems, disappointments, dreams. The culmination of the play is their escape from school and going to the scating rink. On top of this forbidden act they lost a large amount of money that they have to give back (without telling the adults because they will be punished). Thus, the characters experience different trials, revealing their feelings, helping each other, demonstrating friendship, love, determination, as well as envy, bluster, rudeness. Each act of the play develops a separate financial theme, the complex issues are presented in a funny, playful way.